Oligosaccharides and galactosyl cyclitols in seed desiccation tolerance - Obendorf, R.L.
Soluble carbohydrates are one of multiple components required for the acquisition of desiccation tolerance during seed development and maturation. Sucrose and the raffinose series of oligosaccharides have been extensively studied in relation to seed desiccation tolerance. These galactosyl sucrose oligosaccharides are present in viable tissues of many edible seeds, especially the legumes, and contribute to flatulence after ingestion. A reduction in oligosaccharides of the raffinose series is desired by nutritionists but, if present at less than a threshold level, this this may result in reduced desiccation tolerance and storability of seeds. Some seeds that have very low amounts of raffinose and stachyose accumulate galactosyl cyclitols and small amounts of free cyclitols. Galactosyl cyclitols present in various seeds include galactosyl or methyl derivatives of myo-inositol, D-pinitol, D-chiro-inositol, D-ononitol, and scyllo-inositol. Castor bean seeds accumulate galactinol and buckwheat seeds accumulate fagopyritol in addition to sucrose. Fagopyritol accumulation is associated with the acquisition of desiccation tolerance in buckwheat seeds. The galactosyl sucrose and galactosyl cyclitol soluble carbohydrates in maturing seeds have been proposed to have various roles in desiccation tolerance including non-toxic and non-reducing forms of seed storage products and intracellular osmotic agents contributing to the structural stability of organelles, membranes, enzymes and proteins, other macromolecules, and the glassy state. Ether derivatives of cyclitols may form liquid crystals. Methyl ether derivatives of cyclitols may have roles as cryoprotectants, desiccation protectants, and hydroxyl radical scavengers.
Keywords: CYCLITOLS AND GALACTOSYL CYCLITOLS; GALACTINOL SERIES; GALACTOPINITOL SERIES; LOCALIZATION; RAFFINOSE SERIES OLIGOSACCHARIDES; SEED SOLUBLE CARBOHYDRATES